PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013 - MELATI PRATIWI SUDIRJO; INDRA MAULANA (Eqien - Jurnal Ekonomi dan Bisnis, 2016)
Price to Book Value (PBV) or the price per book value ratio is the relationship between the stock market price and book value per share. This ratio indicates the company's ability to create value relative to the amount of capital invested. The higher PBV companies create value for shareholders. This ratio is also used as an indicator in determining the value of shares as consideration for investors in determining investment decisions. This study aimed to examine the effect of the variable Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Dividend Payout Ratio (DPR) to the Price to Book Value.The population in this study is LQ45 categories listed companies in Indonesia Stock Exchange 2010-2013 period as many as 78 companies with sampling using purposive sampling and samples that meet the criteria are as many as 13 companies. The data in this study using panel data regression analysis (fixed effect) is applied with software Eviews 7.1. and hypothesis testing using t-statistic to test the partial coefficient of regression and f-statistic to examine the effect simultaneously with a significance level of 5%.The results showed that the variables PBV DER significantly influence the value of 0.01. ROA variables significantly influence the PBV with a significance value of 0.00. ROE significantly influence the PBV with a significance value of 0.04. But the House did not influence significantly the variables with a significance value of 0.95. Predictive ability of the four variables to the PBV is at 99% as indicated by the R-Squared of 99% while the remaining 1% is influenced by other factors not included in the model study.Keywords: Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Dividend Payout Ratio (DPR), and Price to Book Value (PBV).